Paradigma Biodiversitas dalam Kerangka Legal-Etis-Teleologis: Perbandingan Fiqh Al-Bi'ah dan Undang-Undang Nomor 32 Tahun 2009 - Islami, Nurul; Rifan, Mohamad (JISH: Jurnal Ilmu Syariah dan Hukum, 2026)
The biodiversity crisis in the anthropocene era demands a reconstruction of the environmental law paradigm that goes beyond anthropocentric logic. This study comparatively examines the biodiversity protection paradigm within a legal-ethical-teleological framework by integrating the positive legal norms of Law No. 32/2009 concerning Environmental Protection and Management with the principles of environmental fiqh (fiqh al-bi’ah). This research method uses a normative juridical approach with statutory, conceptual, and comparative approaches.The results of the research indicate that there are points of agreement and disparities between Law 32/2009 and the MUI Fatwa No. 4/2014 both emphasize the importance of protecting ecosystems for the sake of the balance of life, but with different approaches. The Environmental Management and Management Law (UU PPLH) is normative-instrumental (anthropocentric), while the fatwa emphasizes the moral-religious obligation to preserve living creatures. This study's novel approach is a tridimensional legal, ethical, and teleological framework that synergizes positive legal norms with Islamic ethical values and the objectives of maqashid (environmental stewardship). With this research, the concept of maqashid sharia, specifically hifa al-bi'ah (environmental preservation), is proposed as a normative-teleological foundation for reconstructing national environmental law with ecological justice